STRUCTURAL AND MAGNETIC PROPERTIES OF NANOCRYSTALLINE SrFe12O19 HEXAFERRITES PREPARED BY AUTO COMBUSTION METHOD USING MIXED FUELS (International Journal of Food and Nutritional Sciences, 2022)
The nanocrystalline Sr(1-x)CexFe12O19 (x = 0.0, 0.01, 0.3, 0.05, 0.07 and 0.09) M-type hexaferrites have been prepared via auto combustion using mixed fuels. The morphology and compositions were analysed using XRD, FT-IR and FE-SEM techniques. XRD peaks revealed the nanocrystalline nature of the samples having single phase magnetoplumbhite-type hexagonal crystal structure. Strong absorption FT-IR bands observed in range 300 - 1000 cm-1 and the force constant of tetrahedral site is less than octahedral site which shows Ce3+ occupies Sr2+ sites. The FESEM micrographs exhibit the compact magnetic piled up aggregation of nano hexaferrite. The particle size decreased with increase in Ce3+ ion content. The magnetic properties by VSM studies confirmed the hard nature of strontium ferrite with increase in Ce3+ content. It was found that saturation magnetization and magnetic parameters of strontium ferrites decreases with increase of Ce3+ content. Nano-hexaferrites are useful for magnetic recording and memory devices.